Измерение мощности автономных источников СВЧ излучения - Терещенко, А. И. (ХНУРЭ, 2009)
At realization of conditions of radio-electronic means, protection of the information on a radio channel there is a necessity of measurement of capacity of radiation of independent small-sized sources. The aerial of such source, as a rule, is the oscillatory contour and connecting conductors of the scheme. There is no opportunity of connection of the measuring device. Known methods of measurement have essential errors more than 3 dB.
Keywords: автономный источник СВЧ излучения; измерение мощности